1998
DOI: 10.1038/sj.sc.3100694
|View full text |Cite
|
Sign up to set email alerts
|

Faecal incontinence in children with spina bifida: The best conservative treatment

Abstract: Incontinence is one of the major stigmata a ecting the quality of life of the myelodysplastic patient. The appropriate management of the neuropathic bladder has led most patients to survive with good conditions. Major advances have also been made in the treatment of faecal incontinence for enabling patients to achieve their full potential, to become integrated in society and to be as independent as possible. We present the results of the Retrograde Colonic Enema (RCE) in 33 patients su ering neurogenic faecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…The definitions used to define continence/ Transanal irrigation in children and young people L Bray and C Sanders Transanal irrigation in children and young people L Bray and C Sanders incontinence and constipation varied between studies. Definitions and criteria to judge incontinence varied from any episodes or incidences of staining, soiling or faecal incontinence, 4,6,9,11,12,19 soiling once a month, 10 soiling three times a month, 16 not needing to wear pads for stool incontinence 13 to no information being supplied on how the studies had characterised continence or incontinence. 5,14,15,17,18 This review has correlated with the studies, whose report rates of continence were achieved.…”
Section: Effectiveness Of Transanal Irrigation In Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…The definitions used to define continence/ Transanal irrigation in children and young people L Bray and C Sanders Transanal irrigation in children and young people L Bray and C Sanders incontinence and constipation varied between studies. Definitions and criteria to judge incontinence varied from any episodes or incidences of staining, soiling or faecal incontinence, 4,6,9,11,12,19 soiling once a month, 10 soiling three times a month, 16 not needing to wear pads for stool incontinence 13 to no information being supplied on how the studies had characterised continence or incontinence. 5,14,15,17,18 This review has correlated with the studies, whose report rates of continence were achieved.…”
Section: Effectiveness Of Transanal Irrigation In Childrenmentioning
confidence: 99%
“…Transanal irrigation was reported as improving the continence in 346 from 383 (90%) children using transanal irrigation at the point of follow-up in the various studies. 4,6,[9][10][11]14,16,17,19 The reports of continence achieved within this figure ranged from 66% 14 to 100% 11,16 (Table 2).…”
Section: Effectiveness Of Transanal Irrigation In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…25 A subsequent report on the Shandling catheter described the achievement of continence in 32 of 33 patients (aged 5-22 years with spina bifida and faecal incontinence), which was maintained during follow-up of 24-35 months, with the exception of a single child who had undergone three surgical procedures for rectal prolapse. 26 A 30-month follow-up study evaluated TAI with saline using the Enema Continence Catheter in 30 children with spina bifida and in 1 child with SCI. 27 During the study, the proportion of children with continent stools increased from 28 to 94% (Po0.01) and the proportion of constipated stools decreased from 55 to 15% (Po0.01).…”
Section: Efficacy Of Tai In Patients With Sci or Cauda Equinamentioning
confidence: 99%
“…19 Two long-term (10-year) follow-up studies in adults and children 20,21 reported success rates of 50% (n ¼ 32) using a rectal balloon catheter, cone-shaped colostomy tip or other system 20 and of 67% (n ¼ 18) using TAI with Peristeen or a cone-shaped colostomy tip. 21 Although less robust than data in patients with SCI, taken together, these data show that TAI can reduce constipation 27 and achieve faecal continence in both children [23][24][25][26][28][29][30] and adults 31 with spina bifida, achieving an improvement in symptoms, 27 independence 23 and quality of life, 30 and remaining effective in the long term. 16,20,21 Efficacy of TAI in patients with multiple sclerosis and other causes of NBD At present, the majority of data on the efficacy of TAI in patients with multiple sclerosis comes from observational studies ( Table 1).…”
Section: Efficacy Of Tai In Patients With Sci or Cauda Equinamentioning
confidence: 99%